Enrichment of Second Generation Ethanol Concentration Obtained from Napier Grass Pretreated with Sulfuric Acid and Hydrothermal Pretreatment - Phakeenuya Vanarat; Panakkal Elizabeth Jayex; Gundupalli Marttin Paulraj; Klinjapo Roungdao; Sriariyanun Malinee; Tantayotai Prapakorn (E3S Web of Conferences)
Enhancing sugar concentration is crucial for improving ethanol yield in biorefinery processes, enabling more efficient downstream recovery. This study investigates the hydrothermal pretreatment of Napier grass with 2% sulfuric acid to boost sugar recovery and ethanol production by incorporating a concentration step. After pretreatment, the liquid fractions were concentrated two-fold and four-fold through rotary evaporation and freeze-drying, resulting in a significant increase in sugar levels, with a 3.5-fold rise in sugar concentration achieved through rotary evaporation compared to unconcentrated samples. However, ethanol production was limited by elevated levels of inhibitors, such as acetic acid and furfural. The maximum ethanol concentration reached was 2.43%, from a liquid fraction concentrated four-fold. These results highlight the necessity of concentration techniques to improve sugar recovery, while also emphasizing the importance of removing inhibitors to increase ethanol yields and enhance the overall efficiency of biorefining processes.